Synthesis and Characteristics of CdS Nanoparticles in Normal (1 g) and Simulated Microgravity (SMG) - Shinde, P. S.; Adhav, L. D.; Pise, R. M.; Jagtap, S. S. (BULETIN FISIKA; Vol 22 No 1 (2021): BULETIN FISIKA February Edition, 2020)
In the present investigation, the cadmium sulphide (CdS) nanoparticles are synthesized in the normal gravity i.e. 1 g (called as control) and in simulated microgravity (called as SMG). The SMG was created by using an instrument called Random Positioning Machine (RPM). Cadmium sulfide nanoparticles were synthesized by using standard chemical method under normal gravity (1 g) and simulated microgravity conditions. The synthesized CdS nanoparticles were characterized by Ultraviolet Visible spectroscopy, Fourier Transform Infrared Ray spectroscopy (FTIR), X-ray diffraction (XRD). The UV-visible absorption spectrum of CdS nanoparticle solution showed a distinct absorption peak at 472.19 nm in control and 458.26 nm in SMG. The band gap calculated from the absorption edge for microgravity sample was 2.71 eV and for control sample was 2.63 eV.  The crystalline size of CdS nanoparticles synthesised in control and Micro-g was determined by XRD. Obtained results showed smaller the particle size in microgravity sample (10.78 nm) as compared to control sample (13.89 nm).